Model Pemasaran Strategik Perhotelan: Sebuah Makalah Konseptual - Hastjarjo, Kelik (Penerbit Goodwood, 2022)
Purpose: The purpose of this study is to develop a hospitality marketing strategy framework starting from pre-encounter marketing, encounter marketing, and post-encounter marketing. Methodology: This paper based on an analysis and synthesis of the literature relating to pre-encounter marketing, encounter marketing, and post-encounter marketing in hospitality. Gaps in previous research have been identified and a conceptual framework proposed as a consequence. Results: A hypothetical model that describes the salient constructs and relationships between key variables which is a complete package of formal propositions which are logical statements derived from a conceptual framework. Limitations: This paper provides a method for future researchers to implement strategic marketing planning in the hospitality industry through the application of structured dimensions. Contribution: This paper identifies the previously unexplored connection of service quality with service experience and hospitality service encounters between constructions, so that this connection is a new construct to improve hospitality customer satisfaction.